Reaction‐bonded B4C/SiC composites synthesized by microwave heating. Issue 4 (29th March 2019) - Dutto, Mathieu; Goeuriot, Dominique; Saunier, Sébastien; Marinel, Sylvain; Frage, Nachum; Hayun, Shmuel
Abstract: The reaction‐bonding technique was used to synthesize boron carbide (B4 C) ‐ silicon carbide (SiC) composites by microwave heating. Preforms of porous B4 C were obtained by compaction followed or not by partial densification. Then, the material was infiltrated by molten silicon under a microwave heating. The influence of the thermal cycles (T: 1400‐1500°C, t : 5‐120 minutes) is low. The hardness of boron carbide is comparable to that of alumina (15‐19 GPa) for a much lower density (≈2.5 g/cm 3 for B4 C‐based material instead of 3.95 g/cm 3 for alumina). These properties make this composite, obtained by microwave heating, a good candidate for ballistic applications.